Religious orientation and its relation to the academic integrity of postgraduate students (Journal of the College of Basic Education, 2022)
The research aims to identify the differences between the religious and physical orientation of the research sample and the differences in the religious orientation in the research sample according to the variables of gender and specialization، and The academic integrity of the research sample. The differences in academic integrity of the research sample according to the variables of gender and specialization. The relationship between religious orientation and academic integrity in the research sample and prediction، included the sample of the study (120) of postgraduate students from the college of science، engineering، information and political science at the University of Baghdad and were selected by the method of class purpose، and to achieve the research objectives، the two researchers adopted the Religious Orientation Scale for alhajar and Radwan 2006 And the establishment of a measure of academic integrity. The results of the research show that postgraduates have strong religious tendencies that are stronger than the apparent religious trends. There are no statistically significant differences in the religious orientation of the sample according to gender and specialization variables. The research sample adheres to the standards of academic integrity. There are no significant statistical differences in the academic integrity of the research sample according to gender variables and specialization. The fundamental religious orientation contributes to academic integrity in general in the research sample. In light of these results، Several plates.